Isolasi dan Identifikasi Senyawa Seskuiterpen dari Curcuma soloensis Val. (Temu Glenyeh) - Soerya Dewi Marliyana; Muhamad Widyo Wartono; Fajar Rakhman Wibowo; Gesti Munasah (Syarif Hidayatullah State Islamic University, 2018)
Curcuma soloensis Val. is a family plant Zingiberaceae and is known as